Experiences of Fast Queue health care users in primary health care facilities in eThekwini district, South AfricaExperiences of Fast Queue health care users in primary health care facilities in eThekwini district, South Africa - Dudu G. Sokhela; Nonhlanhla J. Makhanya; Nokuthula M. Sibiya; Kathleen M. Nokes (AOSIS, 2013)
Background: Comprehensive Primary Health Care (PHC), based on the principles of accessibility, availability, affordability, equity and acceptability, was introduced in South Africa to address inequalities in health service provision. Whilst the Fast Queue was instrumental in the promotion of access to health care, a major goal of the PHC approach, facilities were not prepared for the sudden influx of clients. Increased access resulted in long waiting times and queues contributing to dissatisfaction with the service which could lead to missed appointments and non-compliance with established treatment plans.Objectives: Firstly to describe the experiences of clients using the Fast Queue strategy to access routine healthcare services and secondly, to determine how the clients' experiences led to satisfaction or dissatisfaction with the Fast Queue service.Method: A descriptive qualitative survey using content analysis explored the experiences of the Fast Queue users in a PHC setting. Setting was first identified based on greatest number using the Fast Queue and geographic diversity and then a convenience sample of health care users of the Fast Queue were sampled individually along with one focus group of users who accessed the Queue monthly for medication refills. The same interview guide questions were used for both individual interviews and the one focus group discussion. Five clinics with the highest number of attendees during a three month period and a total of 83 health care users of the Fast Queue were interviewed. The average participant was female, 31 years old, single and unemployed.Results: Two themes with sub-themes emerged: health care user flow and communication, which highlights both satisfaction and dissatisfaction with the fast queue and queue marshals, could assist in directing users to the respective queues, reduce waiting time and keep users satisfied with the use of sign posts where there is a lack of human resources.Conclusion: Effective health communication strategies contribute to positive experiences by health care users and these can be effected by: (1) involvement of health care providers in planning the construction of health facilities to give input about patient flow, infection prevention and control and provision of privacy, (2) effective complaints mechanisms for users to ensure that complaints are followed up and (3)encouraging users to arrive at the facility throughout the day, rather than the present practice where all users arrive at the clinic early in the morning.